Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.20473/jn.v10i22015.222-232
|View full text |Cite
|
Sign up to set email alerts
|

Individual Reminiscence Therapy can Decrease Depression Level on Elderly at Social Homes

Abstract: Introduction: Aging is a natural process in oldest old. The psychosocial development of the elderly to enhance self-integration. Reminiscence therapy is one of psychosocial treatment for elderly using memory recall of one’s life event in the past. The purpose of this study was to determine the effect of individual reminiscence therapy on depression among elderly in the social homes. Method: The study design was used Quasy-Eksperiment Pre-Post Test with Control Group. A total of 60 elderly people were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Research on the validity of the GDS SF obtained a validity value of 0.89 with high sensitivity to assess depressed patients with high sensitivity to determine depressed patients (Lesher & Berryhill, 1994). The validity test results of the Indonesian version of the GDS-15 questionnaire have r count values of Jurnal Aisyah: Jurnal Ilmu Kesehatan, 5(2), December 2020, -103 Dwi Novitasari; Sidik Awaludin validity ranging from 0.406 to 0.826 and reliability of 0.895 so that they are declared valid and reliable (Hidayati, Mustikasari, & Putri, 2015). Depression category was measured based on the criteria: a total score of 0-4 is not depressed/average, 5-9 is suggestive of depression, and 10 -15 is indicative of depression.…”
Section: Methodsmentioning
confidence: 99%
“…Research on the validity of the GDS SF obtained a validity value of 0.89 with high sensitivity to assess depressed patients with high sensitivity to determine depressed patients (Lesher & Berryhill, 1994). The validity test results of the Indonesian version of the GDS-15 questionnaire have r count values of Jurnal Aisyah: Jurnal Ilmu Kesehatan, 5(2), December 2020, -103 Dwi Novitasari; Sidik Awaludin validity ranging from 0.406 to 0.826 and reliability of 0.895 so that they are declared valid and reliable (Hidayati, Mustikasari, & Putri, 2015). Depression category was measured based on the criteria: a total score of 0-4 is not depressed/average, 5-9 is suggestive of depression, and 10 -15 is indicative of depression.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that reminiscence therapy was an effective therapeutic measure to reduce depression in older women. 21…”
Section: The Depression Level In the Elderly After Is Giving Reminiscence Therapy Through Kidung Bali In Mataram Citymentioning
confidence: 99%